Harnessing the potential of endophytes: Sustainable solutions for enhancing forage crop resilience and soil fertility - Asma Mahjoub; Wiem Mnafgui; Nourhene Maiza; Nour Ressaissi; Ndiko Ludidi; Mounawer Badri (Journal of Oasis Agriculture and Sustainable Development, 2023)
Environmental changes pose significant challenges to sustainable agriculture, adversely affecting crop production and soil fertility. Factors such as drought, salinity, pathogens, and soil type exert their influence on the behavior of fodder crops by altering their morphological, biochemical, and molecular mechanisms, ultimately leading to reduced yields and productivity. Consequently, there is a pressing need to develop mitigation strategies aimed at enhancing the tolerance of forage crops to both biotic and abiotic stresses, addressing a critical challenge in sustaining their growth.